The Determinants Of Information Technology Towards Innovation Performance In Iraqi SMEs - Abdul Raheem, Hayder Adil; Al-Shami, Samer Ali Hussein; Abdul Rashid, Nurulizwa; Jasim Mohammed, Zaid; Raad, Wisam (Blue Eyes Intelligence Engineering and Sciences Publication, 2019)
Information technology has inevitably perceived as a core source for the competitive advantages of SMEs. It facilitates innovation capabilities through transforming the needed knowledge that is important for new product, services, market, organizational and processes development. Yet, the literature on the application of IT on innovation abilities still suffering to empirical research, especially from developing countries. Therefore, this article aims to examine the role of IT infrastructure on innovation capabilities in Iraqi SMEs. The survey was used to gather data and regression analysis carried to analysis the data. The finding of this paper emphasizes that IT infrastructure (IT connectivity, modularity and personal) has positive effect on innovation performance in Iraqi SMEs.